2021
DOI: 10.1177/09544062211042044
|View full text |Cite
|
Sign up to set email alerts
|

Fracture prediction in spin forming of anisotropic metal sheets

Abstract: Fracture often occurs in the spin forming process of thin-walled metal sheets, due to the limited fracture strain and local large plastic deformation of the sheets during the process. However, the accurate fracture prediction is a huge challenge due to the combinations of material anisotropy, complex deformation history and contact boundary conditions in the process. Though there are scattered uncoupled ductile fracture criteria proposed with various deformation mechanisms, reasons for their different fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Hwang et al [ 14 ] studied the fracture mechanism of hydraulic punching by using the NCL damage model and optimized the punch shape in the hydraulic punching process of sPFC590Y carbon steel tubes. Li et al [ 15 ] used the Abaqus with eight commonly used uncoupled damage models to predict the fracture of thin-walled metal plates during room-temperature spinning forming. The results showed that the Oyane and Oh damage models had a more accurate capability to predict fracture in spinning processes.…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al [ 14 ] studied the fracture mechanism of hydraulic punching by using the NCL damage model and optimized the punch shape in the hydraulic punching process of sPFC590Y carbon steel tubes. Li et al [ 15 ] used the Abaqus with eight commonly used uncoupled damage models to predict the fracture of thin-walled metal plates during room-temperature spinning forming. The results showed that the Oyane and Oh damage models had a more accurate capability to predict fracture in spinning processes.…”
Section: Introductionmentioning
confidence: 99%